Anti-aflatoxin potential of phenolic compounds from common beans (Phaseolus vulgaris L.) - León Cortes, Dayana (2025)
Common beans (Phaseolus vulgaris L.) are widely consumed legumes in Latin America and Africa, valued for their nutritional compounds and antioxidants. Their high polyphenol content contributes to the antioxidant properties, with bioactive compounds showing antifungal and antimycotoxin effects. Certain polyphenols, accumulated in the grain coat, exhibit antimicrobial activity. Mycotoxins, produced mainly by fungi of the genera Aspergillus, Fusarium, and Penicillium, pose health risks. This study explores polyphenols in tepary bean and in different common bean varieties, assessing their effect against aflatoxins. In vitro tests were done using grains inoculated with A. flavus to induce mycotoxin production, while polyphenols were extracted from non-inoculated grains. Polyphenol-rich extract reduced aflatoxin B1 produced by the fungus. In most bean varieties, especially red-grain types, the fungus exhibited decreased aflatoxin production, negatively correlating with flavonoids. Catechin was associated with reduced A. flavus toxigenicity. This study highlights beans' potential in mitigating aflatoxin contamination through their phenolic compounds.